Postprandial glycaemia-lowering effect of a green tea cultivar Sunrouge and cultivar-specific metabolic profiling for determining bioactivity-related ingredients. Issue 1 (December 2018) - Wasai, Masafumi; Fujimura, Yoshinori; Nonaka, Haruna; Kitamura, Ryo; Murata, Motoki; Tachibana, Hirofumi
Abstract Although the major green tea catechins can inhibit the activity of carbohydrate-hydrolyzing enzymes, there is a paucity of information describing the potential of other green tea ingredients and numerous green tea cultivars. Herein, we reveled that a green tea cultivar Sunrouge significantly suppressed the postprandial blood glucose level in mice. Unlike the most representative Japanese green tea cultivar, Yabukita, the suppression by Sunrouge was observed clearly during the initial period after oral dosing of starch. Sunrouge also strongly inhibited the carbohydrate-hydrolyzing enzymes α-glucosidase and α-amylase when compared with that of Yabukita and many other cultivars. Liquid chromatography–mass spectrometry (LC–MS)-based metabolic profiling (MP) of 42 Japanese green tea cultivars was performed. Multivariate statistical analysis enabled visualization of the differences among cultivars with respect to their ability to inhibit carbohydrate-hydrolyzing activities. Analysis of metabolites, contributing to the discrimination and prediction of the bioactivity of cultivars, showed thatO -methylated catechins, epicatechin-3-O -(3-O -methyl) gallate (ECG3"Me) and epigallocatechin-3-O -(3-O -methyl) gallate (EGCG3"Me), were newly identified α-glucosidase inhibitors. Such ability was also observed in epigallocatechin-3-O -gallate (EGCG), epicatechin-3-O -gallate (ECG), delphinidin-3-O -glucoside and myricetin-3-O -glucoside. The amounts of these compounds in Sunrouge were higher than that in many other cultivars. These results suggest that Sunrouge has high potential for suppressing the elevation of the postprandial blood glucose level, and an MP approach may become a valuable strategy for evaluating the anti-hyperglycemic activity of green tea and for screening its active ingredients.